Iron status of national-caliber swimmers
Iron deficiency is a possible cause of performance decline. When other analyses do not reveal problems and the swimmer is still highly motivated, it may be worthwhile to have iron analyses conducted to determine if a problem exists. Iron supplementation is a necessary dietary alteration when training at altitude.